Anarchic polysystems. The political translation under the polysystem - Gabriel Torem (Acta Poética, 2015)
In this paper we examine the ability of the polysystem theory to analyze the translation of political texts. Based on the definitions outlined by Even Zohar of culture and centrality concepts, it is concluded that there is a political exclusion of the subject matter. The hypothesis is that, by including in its model translator to a subject acting on the material struggles of political-cultural system, polysystem, as a theory, gain new value and applicability. In this new context, the translator acts on the receptor system as such, but also as an intellectual and activist. An obvious derivation is that the translation stops mere thought of as ancillary activity and passes form a network of relationships in which translator, activist and intellectual are facets of the same subject, here defined as international. Taking the example of political and cultural system the anarchism of the early twentieth century system of Diego Abad de Santillán, who from his activity as leader, journalist, writer and translator, channeled through him stands relations between various subsystems of a kind of macro system international of anarchist movements.